Comparative study of two wet chemical methods of BaSnO3 synthesis: mechanism of formation of mixed oxide - Ochoa Muñoz, Yasser Halil (2015)
Ceramic powders of pure barium stannate (BaSnO3) were synthesized using two wet chemical methods: controlled precipitation and polymeric precursor (Pechini). The obtained ceramic powders were characterized using IR spectroscopy, DTA-TGA, XRD and SEM. Using the precipitation and Pechini methods, single phase BaSnO3 powders were achieved at temperatures of 1250°C and 1000°C respectively-substantially lower than the temperatures required for conventional synthesis (>1350°C). Leading from these results, the physicochemical mechanisms that lead to BaSnO3 formation in the processes of synthesis employed in this work are proposed. This constitutes important information both for determining the advantages and disadvantages of each method and for controlling the characteristics of the powder end product.